Art & creative development for young children - Fox, Jill Englebright; Schirrmacher, Robert; Schirrmacher, Robert 1946- (Australia Wadsworth Cengage Learning, 2012)
A resource for establishing and implementing a developmentally appropriate art program. Written for pre-service and in-service early childhood professionals in child care, preschool, or kindergarten through third grade settings, it takes a child-centered approach to art education. It blends theory and research with practical applications.
1. Understanding creativity -- 2. Creative thinking -- 3. Creative experiences -- 4. Art and the developing child -- 5. Children's artistic development -- 6. The elements of art -- 7. Aesthetics -- 8. Sensory experiences -- 9. The complete early childhood art program -- 10. Child-centered art vs. teacher-directed projects -- 11. Planning, implementing, and evaluating art -- 12. Integrating art across the early childhood curriculum -- 13. The art center -- 14. Art experiences through technology -- 15. Roles, responses and strategies to support children's art -- 16. Art assessment -- App. A. Artistic junk -- App. B. Where to go in your local community for artistic junk -- App. C. Art-related books -- App. D. National standards for arts education -- App. E. Multicultural picture books
Rev. ed. of: Schirrmacher, Robert. Art & creative development for young children. 6th ed. 2009.
Keywords: Art -- Study and teaching (Early childhood) -- United States; Creative ability -- United States; Child development -- United States; Creative activities and seat work; Curriculum planning -- United States